Lithium carboxymethyl cellulose salt, method for producing lithium carboxymethyl cellulose salt, electrode composition for nonaqueous electrolyte secondary batteries, electrode for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

JP2025022258APending Publication Date: 2025-02-14NIPPON PAPER IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023126702
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、高いリチウム転化率を有するカルボキシメチルセルロースリチウム塩およびその製造方法が提供される。また、本発明によれば、このカルボキシセルロースリチウム塩を用いた非水電解質二次電池用電極組成物、非水電解質二次電池用電極、および非水電解質二次電池が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022258000001
    Figure 2025022258000001
Patent Text Reader

Abstract

To provide a lithium carboxymethyl cellulose salt with a high lithium conversion rate.SOLUTION: The present invention provides a lithium carboxymethyl cellulose salt with a carboxymethyl substitution level of 0.5-2.0 per anhydrous glucose unit, where the sodium ion content is 3,000 ppm or less per gram of the lithium carboxymethyl cellulose salt.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium carboxymethyl cellulose salt, a method for producing the lithium carboxymethyl cellulose salt, an electrode composition for a non-aqueous electrolyte secondary battery, an electrode for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. [Background technology]

[0002] In recent years, the rapid spread of small portable devices such as smartphones and tablets, as well as stationary storage batteries, has led to an increasing demand for small batteries with high energy density to power them.

[0003] Generally, graphite-based materials are used for the negative electrodes of lithium-ion secondary batteries, but the theoretical capacity of graphite-based materials is 372 mAh / g (LiC6), which is currently approaching its limit.

[0004] Furthermore, in order to improve the energy density of lithium-ion secondary batteries, it is necessary to select new materials. Therefore, materials made by alloying lithium with silicon, tin, etc., which have the second lowest potential and large specific capacity after carbon and lithium, are attracting attention.

[0005] Among these materials, silicon can absorb up to 4.4 lithium atoms per silicon atom in molar ratio, and theoretically, it can obtain a capacity about 10 times that of graphite-based carbon materials. However, when silicon particles absorb lithium, their volume expands by about 3 to 4 times, and the problem is that repeated charging and discharging causes deterioration and a decrease in capacity. A detailed analysis of this phenomenon has confirmed that when lithium is inserted into an active material containing silicon, the volume expansion causes fine cracks in the electrode, and the electrolyte penetrates into these fine cracks to form a new coating (SEI layer). At this time, irreversible capacity that cannot be restored is generated, and as a result, the battery capacity decreases. This phenomenon appears in the change in charge and discharge efficiency during the cycle. In particular, the decrease in cycle efficiency in the early stage of the cycle, when the volume change is large, has a significant impact on the life of the battery when combined with a positive electrode with high charge and discharge efficiency. Therefore, when using an active material containing silicon, it is an important issue to minimize the change in the electrode structure caused by this volume expansion.

[0006] In view of this situation, Patent Document 1 aims to improve battery characteristics by using a binder that essentially contains three components: carboxymethyl cellulose or a metal salt thereof, polyacrylic acid or a metal salt thereof, and styrene-butadiene rubber or polyvinylidene fluoride. However, according to the examples and comparative examples of Patent Document 1, when only two components (carboxymethyl cellulose and styrene-butadiene rubber, or carboxymethyl cellulose and polyvinylidene fluoride) were used as the binder, the desired battery characteristics were not obtained.

[0007] In addition, in lithium ion secondary batteries, the ions involved in charging and discharging are lithium ions, and it is possible that the presence of other metal ions may degrade the battery characteristics. Therefore, the use of lithium carboxymethylcellulose salt as a metal salt of carboxymethylcellulose has also been considered (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2015-198038 A [Patent Document 2] JP 2023-8785 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, according to the investigations of the present inventors, the conversion rate to lithium salt in Patent Document 2 is low, and further improvement is required.

[0010] An object of the present invention is to provide a lithium carboxymethylcellulose salt having a high lithium conversion rate and a method for producing the same, and to provide an electrode composition for a non-aqueous electrolyte secondary battery, an electrode for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery, which use the lithium carboxymethylcellulose salt. [Means for solving the problem]

[0011] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by a specific procedure.

[0012] That is, according to the present invention, (1) A lithium carboxymethylcellulose salt having a degree of carboxymethyl substitution per anhydrous glucose unit of 0.5 to 2.0, wherein the amount of sodium ions contained in 1 g of the lithium carboxymethylcellulose salt is 3,000 ppm or less. (2) The lithium carboxymethylcellulose salt according to (1), which has a viscosity of a 1% by mass aqueous solution measured at 25°C with a B-type viscometer (30 rpm) of 10 to 20,000 mPa s. (3) A method for producing a lithium carboxymethylcellulose salt, comprising the step of adding a strong acid in an acidification reaction of carboxymethylcellulose or a sodium salt thereof in step (a), wherein the lithium carboxymethylcellulose salt has a degree of carboxymethyl substitution per anhydrous glucose unit of 0.5 to 2.0 and an amount of sodium ions contained in 1 g of the lithium carboxymethylcellulose salt is 3,000 ppm or less; (4) The method for producing a carboxymethylcellulose lithium salt according to (3), wherein the strong acid is nitric acid. (5) A method for producing a carboxymethylcellulose lithium salt according to (3) or (4), comprising the steps of: (b) adding lithium hydroxide in the lithium conversion reaction following the step (a), and then neutralizing with acetic acid; (6) An electrode composition for a non-aqueous electrolyte secondary battery, comprising the lithium carboxymethylcellulose salt according to (1) or (2). (7) An electrode for a non-aqueous electrolyte secondary battery, using the electrode composition for a non-aqueous electrolyte secondary battery according to (6). (8) A non-aqueous electrolyte secondary battery using the electrode composition for a non-aqueous electrolyte secondary battery according to (6). is provided. Effect of the Invention

[0013] According to the present invention, there are provided a carboxymethylcellulose lithium salt having a high lithium conversion rate and a method for producing the same. Also, according to the present invention, there are provided an electrode composition for a non-aqueous electrolyte secondary battery, an electrode for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery, which use the carboxymethylcellulose lithium salt. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The lithium carboxymethyl cellulose salt of the present invention and its production method will be described below.

[0015] The lithium carboxymethylcellulose salt of the present invention is a lithium carboxymethylcellulose salt having a degree of carboxymethyl substitution per anhydrous glucose unit of 0.5 to 2.0, and the amount of sodium ions contained in 1 g of the lithium carboxymethylcellulose salt is 3,000 ppm or less.

[0016] The method for producing a lithium carboxymethylcellulose salt of the present invention includes step (a): adding a strong acid in an acidification reaction of carboxymethylcellulose or its sodium salt, wherein the lithium carboxymethylcellulose salt has a degree of carboxymethyl substitution per anhydrous glucose unit of 0.5 to 2.0 and the amount of sodium ions contained in 1 g of the lithium carboxymethylcellulose salt is 3,000 ppm or less.

[0017] <Carboxymethylcellulose lithium salt> Carboxymethylcellulose or its sodium salt is used as a raw material for producing the carboxymethylcellulose lithium salt (hereinafter sometimes abbreviated as CMC-Li) of the present invention.

[0018] Carboxymethylcellulose or its sodium salt (hereinafter sometimes abbreviated as CMC) can be produced using cellulose as a raw material. Carboxymethylcellulose has a structure in which the hydroxyl groups in the glucose units constituting cellulose are replaced with carboxymethyl ether groups, and may be in the form of a sodium salt.

[0019] In the present invention, cellulose refers to a polysaccharide having a structure in which D-glucopyranose (also simply called "glucose unit" or "anhydroglucose") is linked together through β,1-4 bonds. Cellulose is generally classified into natural cellulose, regenerated cellulose, fine cellulose, microcrystalline cellulose excluding the amorphous region, etc., based on the origin, manufacturing method, etc.

[0020] Examples of natural cellulose include bleached or unbleached pulp, refined linters, and cellulose produced by microorganisms such as acetic acid bacteria. The raw material for bleached or unbleached pulp is not particularly limited, and examples thereof include wood, cotton, straw, bamboo, and the like. The method for producing bleached or unbleached pulp is also not particularly limited, and examples thereof include mechanical methods, chemical methods, and methods that combine mechanical and chemical methods. Examples of bleached or unbleached pulp include mechanical pulp, chemical pulp, groundwood pulp, sulfite pulp, kraft pulp, and pulp for papermaking. Examples of bleached or unbleached pulp also include dissolving pulp, which is chemically refined and mainly dissolved in chemicals for use, and is the main raw material for artificial fibers, cellophane, and the like.

[0021] An example of regenerated cellulose is regenerated cellulose obtained by dissolving cellulose in a solvent such as a cuprammonium solution, a cellulose xanthate solution, or a morpholine derivative, and then spinning the solution again.

[0022] Examples of fine cellulose include fine cellulose obtained by depolymerizing cellulosic materials such as natural cellulose and regenerated cellulose through acid hydrolysis, alkali hydrolysis, enzymatic decomposition, crushing treatment, vibrating ball mill treatment, etc., and fine cellulose obtained by mechanically treating cellulosic materials.

[0023] A known method can be used to produce carboxymethyl cellulose or its sodium salt. For example, cellulose is treated with a mercerizing agent (alkali) to prepare mercerized cellulose (alkali cellulose), and then an etherifying agent is added to the mercerized cellulose to cause an etherification reaction, thereby producing carboxymethyl cellulose or its sodium salt.

[0024] The cellulose raw material can be any of the above-mentioned cellulose raw materials without any particular limitations, but cellulose raw materials with high cellulose purity are preferred, and dissolving pulp or linter are more preferred. By using these, carboxymethylcellulose or its sodium salt with high purity can be obtained.

[0025] Examples of the mercerizing agent include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, etc. Examples of the etherifying agent include monochloroacetic acid, sodium monochloroacetate, etc.

[0026] In a general method for producing water-soluble carboxymethylcellulose or its sodium salt, the molar ratio of the mercerizing agent to the etherifying agent (mercerizing agent / etherifying agent) is generally 2.00 to 2.45 when monochloroacetic acid is used as the etherifying agent. The reason is that when the molar ratio is 2.00 or more, the etherification reaction can be sufficiently carried out, and the unreacted monochloroacetic acid can be prevented from being wasted. When the molar ratio is 2.45 or less, the side reaction caused by the excess mercerizing agent and monochloroacetic acid can be prevented from proceeding to produce an alkali metal glycolate, which is economical.

[0027] In the present invention, the carboxymethylcellulose or the sodium salt thereof may be a commercially available product, for example, "Sunrose" manufactured by Nippon Paper Industries Co., Ltd.

[0028] (Degree of substitution of carboxymethyl group in CMC) The degree of substitution of carboxymethyl groups per anhydrous glucose unit of carboxymethyl cellulose or its sodium salt used as a raw material (hereinafter sometimes referred to as DS value) is preferably 0.5 to 2.0. By having a DS value of 0.5 or more, it is possible to maintain good solubility in water and suppress the generation of undissolved matter. In addition, by having a DS value of 2.0 or less, it is possible to suppress an increase in spinnability of the liquid and maintain easy handling. Therefore, the DS value of carboxymethyl cellulose or its sodium salt used as a raw material is preferably 0.5 to 2.0, more preferably 0.55 to 1.5, and even more preferably 0.6 to 1.0.

[0029] The degree of substitution of the carboxymethyl group is measured as follows: Weigh out approximately 2.0 g of sample and place it in a 300 mL Erlenmeyer flask with a stopper. Add 100 mL of a solution of 100 mL of concentrated nitric acid in 1000 mL of methanol, shake for 3 hours, and convert the salt of carboxymethylcellulose (CMC) to H-CMC (hydrogen-type carboxymethylcellulose). Weigh out 1.5 to 2.0 g of the bone-dry H-CMC and place it in a 300 mL Erlenmeyer flask with a stopper. Moisten the H-CMC with 15 mL of 80% methanol, add 100 mL of 0.1 N-NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N-H2SO4, and calculate the degree of carboxymethyl substitution (DS value) using the following formula. A = [(100 × F'-0.1N-H2SO4 (mL) × F) × 0.1] / (bone dry mass of H-CMC (g)) Degree of carboxymethyl substitution = 0.162 x A / (1-0.058 x A) F': Factor of 0.1N-H2SO4 F: Factor of 0.1N-NaOH

[0030] (CMC Viscosity) The viscosity of a 1% by mass aqueous solution of carboxymethyl cellulose or its sodium salt used as a raw material, measured at 25° C. with a Brookfield viscometer (30 rpm), is preferably 10 to 20,000 mPa s, more preferably 500 to 10,000 mPa s, and even more preferably 1,000 to 10,000 mPa s. If this viscosity is too high, there is a problem of poor coatability onto electrode plates, and if it is too low, there is a problem of low adhesive strength to electrode plates.

[0031] The viscosity was measured as follows: Carboxymethylcellulose or its sodium salt is weighed into a 1,000 mL glass beaker and dispersed in 900 mL of distilled water to prepare an aqueous dispersion with a solid content of 1% (w / v). The aqueous dispersion is stirred at 600 rpm for 3 hours at 25°C using a stirrer. The viscosity is then measured after 3 minutes at a rotation speed of 30 rpm using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.) according to the method of JIS-Z-8803.

[0032] (Step (a)) The method for producing CMC-Li of the present invention includes step (a): adding a strong acid in the acidification reaction of carboxymethyl cellulose or a sodium salt thereof.

[0033] Examples of strong acids added in the acidification reaction include nitric acid, hydrochloric acid, and sulfuric acid. Nitric acid is preferably used because it is less likely to corrode metals and therefore can prevent metal contamination in the resulting CMC-Li.

[0034] The acidification reaction is preferably carried out in the presence of a strong acid, carboxymethylcellulose or a salt thereof in a solvent or dispersion medium containing an alcohol such as methanol, ethanol, isopropyl alcohol, etc. In the acidification reaction, the concentration of the alcohol such as methanol in the solvent or dispersion medium is preferably 80 to 95 vol%. The acidification reaction is preferably carried out under stirring conditions at room temperature for about 1 to 3 hours, and may be further stirred, filtered, or dried as necessary.

[0035] When sodium carboxymethylcellulose is used as a raw material, 100% of the Na carboxymethyl groups can be converted to the H type by undergoing step (a).

[0036] (Step (b)) In addition, the method for producing CMC-Li of the present invention preferably includes a step of adding lithium hydroxide in the lithiation reaction after step (a) and then neutralizing with acetic acid.

[0037] Specifically, lithium hydroxide is added to the H-type carboxymethylcellulose (CMC-H) obtained in the above step (a) to carry out a lithiation reaction, and then neutralization is carried out using acetic acid.

[0038] The lithiation reaction is preferably carried out in a solvent or dispersion medium containing an alcohol such as methanol, ethanol, isopropyl alcohol, etc. The lithiation reaction is preferably carried out under stirring conditions at room temperature for about 1 to 3 hours. In addition, the concentration of the alcohol in the solvent or dispersion medium in the acidification reaction is preferably 55 to 95 vol%. In addition, the solvent or dispersion medium may contain water, etc. In addition, it is preferable that the pH after neutralization with acetic acid is 6 to 8. Furthermore, stirring, filtration, and drying may be carried out as necessary.

[0039] (Sodium ion content) By passing through step (b), CMC-Li with a conversion rate to Li of about 100% can be obtained. Here, the sodium ion content of the CMC-Li of the present invention is 3,000 ppm or less, preferably 1 to 3,000 ppm, more preferably 1 to 2,000 ppm, and further preferably 1 to 1,000 ppm. In other words, the small sodium ion content indicates a high conversion rate to Li. The sodium ion content was measured by placing 1 g of CMC-Li in a crucible, heating it in an electric furnace at 500°C for 1 to 3 hours, cooling it to room temperature, adding 1 ml of 6N hydrochloric acid, and evaporating it on a hot plate at 100°C until the solvent disappeared. After cooling it to room temperature, 1 ml of 6N hydrochloric acid was added again, and the crucible was heated on a hot plate at 50°C for about 10 minutes. After cooling it to room temperature, ultrapure water was added to it, and it was transferred to a 50 ml measuring flask, and further ultrapure water was added to make the volume constant to 50 ml. The solution prepared in this way can be measured by ion chromatography.

[0040] (Degree of substitution of carboxymethyl group in CMC-Li) The CMC-Li of the present invention has a degree of substitution of carboxymethyl groups per anhydrous glucose unit (hereinafter sometimes referred to as DS value) of 0.5 to 2.0. When the DS value is 0.5 or more, the dispersibility of active materials and the like can be exhibited. Also, when the DS value is 2.0 or less, the adhesive strength to the electrode plate can be exhibited. Therefore, the DS value of the CMC-Li of the present invention is 0.5 to 2.0, preferably 0.55 to 1.5, and more preferably 0.6 to 1.0.

[0041] The degree of substitution of the carboxymethyl group is measured as follows: Weigh out approximately 2.0 g of sample and place it in a 300 mL Erlenmeyer flask with a stopper. Add 100 mL of a solution of 100 mL of concentrated nitric acid in 1000 mL of methanol, shake for 3 hours, and convert the salt of carboxymethylcellulose (CMC) to H-CMC (hydrogen-type carboxymethylcellulose). Weigh out 1.5 to 2.0 g of the bone-dry H-CMC and place it in a 300 mL Erlenmeyer flask with a stopper. Moisten the H-CMC with 15 mL of 80% methanol, add 100 mL of 0.1 N-NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N-H2SO4, and calculate the degree of carboxymethyl substitution (DS value) using the following formula. A = [(100 × F'-0.1N-H2SO4 (mL) × F) × 0.1] / (bone dry mass of H-CMC (g)) Degree of carboxymethyl substitution = 0.162 x A / (1-0.058 x A) F': Factor of 0.1N-H2SO4 F: Factor of 0.1N-NaOH

[0042] In addition, since the above measurement method is used, the degree of substitution of the carboxymethyl group in CMC-Li is the same as the degree of substitution of the carboxymethyl group per anhydrous glucose unit in the carboxymethyl cellulose or its sodium salt used as the raw material.

[0043] (Viscosity of CMC-Li) The viscosity of a 1% by mass aqueous solution of the CMC-Li thus obtained, measured at 25°C with a Brookfield viscometer (30 rpm), is preferably 10 to 20,000 mPa·s, more preferably 500 to 10,000 mPa·s, and even more preferably 1,000 to 10,000 mPa·s. If the viscosity is too high, there is a problem of poor coatability. If the viscosity is too low, there is a problem of low adhesive strength to the electrode plate.

[0044] The viscosity was measured as follows: CMC-Li is weighed into a 1,000 mL glass beaker and dispersed in 900 mL of distilled water to prepare an aqueous dispersion with a solid content of 1% (w / v). The aqueous dispersion is stirred at 600 rpm for 3 hours at 25°C using a stirrer. The viscosity is then measured after 3 minutes at 30 rpm using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.) according to the method of JIS-Z-8803.

[0045] The CMC-Li of the present invention has a high lithium conversion rate. Specifically, the conversion rate is nearly 100%. In addition, when used in a battery, it can prevent the inclusion of other metals. Furthermore, when used in a battery, it can improve the battery capacity.

[0046] <Binder for non-aqueous electrolyte secondary battery> The CMC-Li of the present invention is used as an electrode binder for a non-aqueous electrolyte secondary battery. Usually, an aqueous solution containing CMC-Li is used as an electrode binder for a non-aqueous electrolyte secondary battery. The concentration of CMC-Li in the aqueous solution of CMC-Li is usually 0.1 to 10 mass %, preferably 0.2 to 4 mass %, and more preferably 0.5 to 2 mass %.

[0047] There are no particular limitations on the conditions for producing an aqueous solution of CMC-Li. For example, carboxymethylcellulose and / or a salt thereof are added to water (e.g., distilled water, purified water, tap water, etc.) and dissolved by stirring, etc., as necessary, to prepare the aqueous solution.

[0048] In addition, the binder for the non-aqueous electrolyte secondary battery may include other binders in addition to CMC-Li. Examples of binders used in the electrode composition for the negative electrode include carboxymethyl cellulose, carboxymethyl cellulose salts (excluding lithium salts), and synthetic rubber-based binders. As the synthetic rubber-based binder, one or more selected from the group consisting of styrene butadiene rubber (SBR), nitrile butadiene rubber, methyl methacrylate butadiene rubber, chloroprene rubber, carboxy-modified styrene butadiene rubber, and latexes of these synthetic rubbers can be used. Among these, styrene butadiene rubber (SBR) is preferred. Examples of binders used in the electrode composition for the positive electrode include polytetrafluoroethylene (PTFE) in addition to the synthetic rubber-based binders listed as the binders for the negative electrode.

[0049] <Electrode composition for nonaqueous electrolyte secondary batteries> The electrode composition for a non-aqueous electrolyte secondary battery of the present invention (hereinafter sometimes referred to as "electrode composition") ) contains at least an electrode active material and the CMC-Li of the present invention as the binder for the non-aqueous electrolyte secondary battery.

[0050] That is, the CMC-Li of the present invention can be used as an electrode binder to constitute an electrode composition together with an electrode active material. In this case, the content of carboxymethylcellulose and / or a salt thereof in the electrode composition is preferably 0.1 to 4.0% by mass based on the total amount of the electrode composition.

[0051] When the other binders are used, the content of the binder for non-aqueous electrolyte secondary batteries in the electrode composition is preferably 1 to 10 mass %, more preferably 1 to 6 mass %, and even more preferably 1 to 2 mass %.

[0052] (electrode active material) The electrode active material contained in the composition for a nonaqueous electrolyte secondary battery is a negative electrode active material when the electrode for a nonaqueous electrolyte secondary battery is a negative electrode, and is a positive electrode active material when the electrode is a positive electrode.

[0053] As the negative electrode active material, graphitic materials such as graphite (natural graphite, artificial graphite, etc.), coke, and carbon fiber; elements capable of forming an alloy with lithium, that is, for example, elements such as silicon-based compounds, Al, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Ti; compounds containing elements capable of forming an alloy with lithium; composites of elements capable of forming an alloy with lithium and the said compounds with carbon and / or the said graphitic materials, or nitrides containing lithium, etc. can be exemplified. Among these, graphitic materials and silicon-based compounds are preferable, and silicon particles or silicon oxide particles are more preferable as the graphite and silicon-based compounds.

[0054] Note that the silicon oxide in the present invention means SiO x (represented by 0 < x ≦ 2). Also, in the present invention, as the electrode layer, a composite of a silicon-based compound and a graphitic material can also be used.

[0055] When the negative electrode active material is a composite of a graphitic material and a silicon-based compound, the mixing ratio of the graphitic material:silicon-based compound is preferably 10:90 to 90:10, and more preferably 50:50 to 80:20.

[0056] As the positive electrode active material, LiFePO4, LiMe x O y (Me means a transition metal containing at least one of Ni, Co, and Mn. x and y mean arbitrary numbers.)-based positive electrode active materials are preferable.

[0057] The content of the electrode active material in the electrode layer is usually 90 to 99% by mass, preferably 91 to 99% by mass, more preferably 92 to 99% by mass, still more preferably 95 to 99% by mass, particularly preferably 96 to 99% by weight, and most preferably 98 to 99% by mass.

[0058] The electrode composition may contain a conductive assistant as necessary. Examples of the conductive assistant include conductive carbon such as carbon black, acetylene black, and ketjen black. The content of the conductive assistant in the electrode composition is usually 0.01 to 20% by mass, and preferably 0.1 to 10% by mass.

[0059] The solvent used in the electrode composition is preferably an aqueous solvent. The type of aqueous solvent is not particularly limited, but is preferably water, a water-soluble organic solvent, or a mixed solvent thereof, and more preferably water.

[0060] The water-soluble organic solvent is an organic solvent that dissolves in water. Examples of the water-soluble organic solvent include methanol, ethanol, 2-propanol, butanol, glycerin, acetone, methyl ethyl ketone, 1,4-dioxane, N-methyl-2-pyrrolidone, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), N,N-dimethylacetamide, dimethyl sulfoxide (DMSO), acetonitrile, methyl triglycol succinate, acetic acid, and combinations thereof.

[0061] When the mixed solvent is used as the aqueous solvent, the amount of the water-soluble organic solvent in the mixed solvent is preferably 10% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more. The upper limit of the amount is not limited, but is preferably 95% by mass or less, and more preferably 90% by mass or less. In addition, the aqueous solvent may contain a non-water-soluble organic solvent within a range that does not impair the effects of the invention.

[0062] The conditions for producing the electrode composition are not particularly limited. For example, other components constituting the electrode composition are added to an aqueous solution of carboxymethylcellulose and / or a salt thereof, and mixed with stirring as necessary. The form of the electrode composition is not particularly limited, and may be any of a liquid, a paste, a slurry, and the like.

[0063] <Non-aqueous electrolyte secondary battery electrode> The electrode composition can be applied onto the current collector to form an electrode layer on the current collector. Examples of the application method include blade coating, bar coating, and die coating, and blade coating is preferred. For example, in the case of blade coating, a method of casting the electrode composition onto the current collector using a coating device such as a doctor blade is exemplified. In addition, the lamination method is not limited to the above specific example, and a method of discharging the electrode composition from an extrusion type injector having a slot nozzle onto a current collector wound around a backup roll and running is also exemplified. In blade coating, the electrode layer can be obtained by further drying by heating (for example, 80 to 120°C, heating time, for example, 4 to 12 hours) or applying pressure by a roll press, etc., as necessary, after casting.

[0064] The shape of the electrode for the non-aqueous electrolyte secondary battery of the present invention is not particularly limited, but is usually a sheet. The thickness of the sheet-shaped electrode plate (the thickness of the electrode layer formed from the electrode composition, excluding the current collector portion) is difficult to specify because it depends on the composition of the composition and the manufacturing conditions, but is usually 30 to 150 μm.

[0065] (current collector) Any electrical conductor that does not cause a fatal chemical reaction in the constructed electrode or battery can be used as the current collector. When the electrode is a negative electrode, a negative current collector can be used, and when the electrode is a positive electrode, a positive current collector can be used.

[0066] Examples of materials for the negative electrode current collector include stainless steel, nickel, copper, titanium, carbon, copper or stainless steel having carbon, nickel, titanium or silver attached thereto, etc. Among these, copper or a copper alloy is preferred, and copper is more preferred. Examples of materials for the positive electrode current collector include metals such as aluminum and stainless steel, with aluminum being preferred. The shape of the current collector can be, for example, a mesh, a punched metal, a foam metal, or a foil processed into a plate shape, with a foil processed into a plate shape being preferred.

[0067] <Nonaqueous electrolyte secondary battery> The electrode for a non-aqueous electrolyte secondary battery of the present invention is used as an electrode for a non-aqueous electrolyte secondary battery. That is, the present invention also provides a non-aqueous electrolyte secondary battery. The non-aqueous electrolyte secondary battery may have a structure in which positive electrodes and negative electrodes are alternately stacked with separators interposed therebetween and wound many times. The laminate of the positive electrodes, separators, and negative electrodes wound many times is placed in a battery container, and a non-aqueous electrolyte is injected and sealed to obtain a non-aqueous electrolyte secondary battery.

[0068] The shape of the nonaqueous electrolyte secondary battery is not particularly limited, and may be a cylindrical type, a square type, a flat type, a coin type, a button type, a sheet type, etc. The material of the battery container is not particularly limited as long as it can prevent moisture from entering the battery, and examples of the material include a laminate of metal, aluminum, etc.

[0069] The separator is usually impregnated with a non-aqueous electrolyte. As the separator, for example, a microporous membrane or a nonwoven fabric made of a polyolefin such as polyethylene or polypropylene can be used.

[0070] The non-aqueous electrolyte usually contains a lithium salt and a non-aqueous solvent. Examples of the lithium salt include LiPF6, LiAsF6, LiBF4, and LiClO4. Examples of the non-aqueous solvent include ethylene carbonate, diethyl carbonate, dimethyl carbonate, propylene carbonate, butylene carbonate, and methyl ethyl carbonate. The non-aqueous solvent may be used alone or in combination of two or more. The concentration of the lithium salt in the non-aqueous electrolyte is usually 0.5 to 2.5 mol / L.

[0071] The electrode for a non-aqueous electrolyte secondary battery and the non-aqueous electrolyte secondary battery produced from the electrode composition using the CMC-Li of the present invention as an electrode binder for a non-aqueous electrolyte secondary battery have excellent battery characteristics such as improved battery capacity. EXAMPLES

[0072] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited thereto. <Measurement and evaluation methods> In the present examples and comparative examples, the indices of the lithium salt of carboxymethyl cellulose were measured by the following methods.

[0073] <Method for measuring the degree of carboxymethyl substitution (CM-DS)> Approximately 2.0 g of a sample of the ground lithium carboxymethylcellulose salt was weighed out and placed in a 300 mL Erlenmeyer flask with a stopper. 100 mL of a solution of 1,000 mL of methanol and 100 mL of concentrated nitric acid was added and shaken for 3 hours to convert the carboxymethylcellulose salt (CMC salt) to H-CMC (carboxymethylcellulose). 1.5 to 2.0 g of bone-dried H-CMC was weighed out and placed in a 300 mL Erlenmeyer flask with a stopper. The H-CMC was moistened with 15 mL of 80% methanol, 100 mL of 0.1 N NaOH was added, and the mixture was shaken at room temperature for 3 hours. Excess NaOH was back-titrated with 0.1 N H2SO4 using phenolphthalein as an indicator. CM-DS was calculated using the following formula 1. (Formula 1) A = [(100 x F - (0.1N H2SO4 (mL)) x F') x 0.1] / (bone dry mass of H-CMC (g)) Carboxymethyl substitution degree (CM-DS) = 0.162 x A / (1-0.058 x A) A: The amount of 1N NaOH required to neutralize 1g of H-CMC (mL) F': Factor of 0.1N H2SO4 F: Factor of 0.1N NaOH

[0074] <Viscosity> Carboxymethylcellulose lithium salt was weighed into a 1,000 mL glass beaker and dispersed in 900 mL of distilled water to prepare an aqueous dispersion with a solid content of 1% (w / v). The aqueous dispersion was stirred at 600 rpm for 3 hours at 25°C using a stirrer. The viscosity was then measured after 3 minutes at a rotation speed of 30 rpm using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.) according to the method of JIS-Z-8803.

[0075] <Metal corrosion> The weight of a SUS304 test piece (50 mm x 50 mm, 20 mm thick) was measured.The test piece was then immersed in 6 wt% nitric acid, 6 wt% hydrochloric acid, and 6 wt% acetic acid, and left to stand at room temperature for one week.The weight was then measured again, and the metal corrosion was evaluated according to the following criteria. ○…Weight loss rate after immersion in acid is less than 0.1wt% ×…Weight loss rate after immersion in acid is 0.1wt% or more

[0076] <Measurement of sodium ion content> The sodium ion content was measured by placing 1 g of CMC-Li in a crucible, heating it in an electric furnace at 500°C for 1 to 3 hours, cooling it to room temperature, adding 1 ml of 6N hydrochloric acid, and evaporating it on a hot plate at 100°C until the solvent disappeared. After cooling it to room temperature, 1 ml of 6N hydrochloric acid was added again, and the crucible was heated on a hot plate at 50°C for about 10 minutes. After cooling it to room temperature, ultrapure water was added to it, and it was transferred to a 50 ml measuring flask, and further ultrapure water was added to make the volume constant to 50 ml. The solution prepared in this way was measured by ion chromatography.

[0077] In addition, the coin-type nonaqueous electrolyte secondary batteries obtained in the examples and comparative examples were evaluated as follows.

[0078] <Battery evaluation> (Discharge capacity (charge / discharge rate test)) The charge and discharge rate tests of the coin-type nonaqueous electrolyte secondary batteries obtained in the examples and comparative examples were carried out by Using Nagano BTS2004, a coin-type non-aqueous electrolyte secondary battery was placed in a thermostatic chamber at 25°C. A total of 52 cycles were performed, with one cycle being a charge and discharge cycle. The charging conditions were constant current, constant voltage (CC-CV) for all cycles. ) method (CC current 0.2C, CV voltage 4.2V, final current 0.02C). As a condition for the discharge treatment, the final voltage was set to 3.0 V. In the first cycle, the discharge treatment was performed at a constant current of 0.2 C, and the discharge capacity (mAh / g) after one cycle was measured. From then until the 52nd cycle, set the constant current for the discharge process as follows. After discharge, the discharge capacity (mAh / g) was measured. (Constant current for discharge treatment in each cycle) 2 to 10 cycles: Discharge treatment at a constant current of 0.2C 11 to 20 cycles: constant current 1C for discharge treatment 21 cycles: Discharge treatment at constant current of 0.2C 22 to 31 cycles: constant current 2C for discharge treatment 32 cycles: Discharge treatment at constant current of 0.2C 33-42 cycles: constant current 3C for discharge treatment 43~52 cycles: constant current 0.2C for discharge treatment

[0079] Example 1 <Preparation of sodium salt of carboxymethylcellulose> A twin-axis kneader with the rotation speed adjusted to 100 rpm was charged with 2720 g of isopropyl alcohol, 170 g of sodium monochloroacetate, and 58 g of sodium hydroxide dissolved in 480 g of water, and 160 g of linter pulp was added after drying for 60 minutes at 30°C. Mercerized cellulose was prepared by stirring and mixing for 90 minutes at 30°C, and then the temperature was raised to 70°C and carboxymethylation reaction was carried out for 90 minutes. After the reaction was completed, the mixture was neutralized with acetic acid to a pH of about 7, deliquored, dried, and pulverized to obtain sodium carboxymethyl cellulose 1 (hereinafter sometimes referred to as CMC1), which has a carboxymethyl substitution degree of 0.70 and a viscosity of a 1% by mass aqueous solution of 7,900 mPa·s measured with a B-type viscometer at 25°C.

[0080] <Step (a) (Preparation of H-type carboxymethylcellulose)> 100mL of 10vol% nitric acid methanol solution and 10g of CMC1 were added to a 200mL beaker and stirred at room temperature for 2 hours. After the reaction was completed, filtration was performed. 200mL of 80vol% methanol aqueous solution and the filtration residue were added to a 300mL beaker, stirred at room temperature for 30 minutes, and filtered. This operation was repeated once. Then, 100mL of methanol and the filtration residue were added to a 200mL beaker, stirred at room temperature for 30 minutes, filtered, and the filtration residue was dried at 105°C for 2 hours to obtain H-type carboxymethylcellulose (hereinafter sometimes referred to as CMC-H1).

[0081] <Step (b) (Preparation of CMC-Li)> 50 mL of 75 vol% aqueous methanol solution and 1.75 g of lithium hydroxide were added to a 200 mL beaker, and the mixture was stirred at room temperature for 1 hour to dissolve the lithium hydroxide. 5 g of H-type carboxymethylcellulose obtained in step (a) was added to the solution, and the mixture was stirred at room temperature for 3 hours. After the reaction was completed, 80 wt% acetic acid was added until the pH of the reaction solution reached 7.0, and the mixture was filtered. Then, 90 vol% aqueous methanol solution and the filtration residue were added to a 100 mL beaker, and the mixture was stirred at room temperature for 30 minutes and filtered twice. The filtration residue was dried overnight at 80°C to obtain carboxymethylcellulose lithium salt 1 (hereinafter sometimes referred to as CMC-Li1). The degree of carboxymethyl substitution of CMC-Li1 was 0.70, and the viscosity of a 1 mass% aqueous solution measured with a B-type viscometer at 25°C was 2,210 mPa·s.

[0082] <Preparation of negative electrode plate> Negative electrode materials: SiOx, acetylene black (manufactured by Stream Chemical) , CMC-Li1, and styrene butadiene rubber (SBR, manufactured by ENEOS Materials, product number TRD 104A) were mixed so that the solid weight ratio was 97:0.5:1.0:1.5, water was added so that the slurry concentration was 45.6 mass%, and the mixture was thoroughly stirred using a Mazerustar (manufactured by Kurabo Industries, KK-250S) to obtain slurry 1. This slurry was applied to a copper foil (manufactured by Furukawa Electric Co., Ltd., NC-WS) measuring 320 mm in length, 170 mm in width, and 17 μm in thickness using an applicator, and then air-dried for 30 minutes, and then dried in a dryer at 60° C. for 30 minutes. The mixture was then pressed using a small tabletop roll press (manufactured by Tester Sangyo Co., Ltd., SA-602) under conditions of 5 kN and a roll peripheral speed of 50 m / min, resulting in a coating weight of 19.7 g / m 2 Thus, a negative electrode plate 1 having an effective discharge capacity of 2100 mAh / g was obtained.

[0083] <Preparation of coin-type non-aqueous electrolyte secondary battery> The obtained negative electrode plate 1 and a LiCoO2 positive electrode plate (manufactured by Hosensha, basis weight 110.2 g / m 2 The negative and positive electrode plates were then vacuum dried at 120° C. for 12 hours.

[0084] Similarly, a separator (manufactured by CS Tech, a polypropylene separator having a thickness of 20 μm) was punched out to have a diameter of 17 mm, and vacuum dried at 60° C. for 12 hours.

[0085] Then, the negative electrode plate 1 was placed in a stainless steel circular dish-shaped container with a diameter of 20.0 mm, and then a separator, a positive electrode plate, a spacer (diameter 15.5 mm, thickness 1 mm), and a stainless steel washer (manufactured by Hosen Co., Ltd.) were stacked in this order, and then 300 μL of electrolyte (1 mol / L LiPF6, ethylene carbonate and diethyl carbonate volume ratio 1:1) was added to the circular dish-shaped container. A stainless steel cap was placed over this via a polypropylene packing, and the container was sealed with a coin battery crimping machine (Hosen Co., Ltd.) to obtain a coin-shaped nonaqueous electrolyte secondary battery 1.

[0086] Example 2 <Preparation of sodium salt of carboxymethylcellulose> A twin-screw kneader with the rotation speed adjusted to 100 rpm was charged with 1,110 g of isopropyl alcohol, 299 g of sodium monochloroacetate, and 101 g of sodium hydroxide dissolved in 147 g of water, and 200 g of linter pulp was added based on the dry weight after drying at 30°C for 60 minutes. The mixture was stirred and mixed at 30°C for 90 minutes to prepare mercerized cellulose, and then heated to 70°C and allowed to undergo a carboxymethylation reaction for 90 minutes. After the reaction was completed, the mixture was neutralized with acetic acid to a pH of about 7, deliquored, dried, and pulverized to obtain sodium carboxymethylcellulose 2 (hereinafter sometimes referred to as CMC2), which has a carboxymethyl substitution degree of 1.34 and a viscosity of a 1% by weight aqueous solution measured with a B-type viscometer at 25°C of 2,020 mPa·s.

[0087] Except for using CMC2 instead of CMC1, steps (a) and (b), the preparation of a negative electrode plate, and the preparation of a coin-type nonaqueous electrolyte secondary battery were carried out in the same manner as in Example 1. The degree of carboxymethyl substitution of carboxymethyl cellulose lithium salt (CMC-Li2) obtained using CMC2 was 1.34, and the viscosity of a 1% by mass aqueous solution measured with a B-type viscometer at 25°C was 629 mPa s.

[0088] Example 3 <Step (a) (Preparation of H-type carboxymethylcellulose)> 100mL of 10vol% hydrochloric acid in methanol and 10g of CMC1 were added to a 200mL beaker and stirred at room temperature for 2 hours. After the reaction was completed, filtration was performed. 200mL of 75vol% aqueous methanol solution and the filtration residue were added to a 300mL beaker, stirred at room temperature for 30 minutes, and filtered. This operation was repeated twice. Then, 100mL of methanol and the filtration residue were added to a 200mL beaker, stirred at room temperature for 30 minutes, filtered, and the filtration residue was dried at 105°C for 2 hours to obtain H-type carboxymethylcellulose (hereinafter sometimes referred to as CMC-H3).

[0089] Except for using CMC-H3 instead of CMC-H1, the process (b), the preparation of a negative electrode plate, and the preparation of a coin-type nonaqueous electrolyte secondary battery were carried out in the same manner as in Example 1. The degree of carboxymethyl substitution of CMC-Li3 was 0.70, and the viscosity of a 1% by mass aqueous solution measured with a B-type viscometer at 25°C was 8,530 mPa s.

[0090] Comparative Example 1 <Step (a) (Preparation of H-type carboxymethylcellulose)> 100mL of 10vol% acetic acid in methanol and 10g of CMC1 were added to a 200mL beaker and stirred at room temperature for 2 hours. After the reaction was completed, filtration was performed. 200mL of 75vol% aqueous methanol solution and the filtration residue were added to a 300mL beaker, stirred at room temperature for 30 minutes, and filtered. This operation was repeated twice. Then, 100mL of methanol and the filtration residue were added to a 200mL beaker, stirred at room temperature for 30 minutes, filtered, and the filtration residue was dried at 105°C for 2 hours to obtain H-type carboxymethylcellulose (hereinafter sometimes referred to as CMC-H4).

[0091] Except for using CMC-H4 instead of CMC-H1, the step (b), the preparation of a negative electrode plate, and the preparation of a coin-type nonaqueous electrolyte secondary battery were carried out in the same manner as in Example 1. The degree of carboxymethyl substitution of carboxymethyl cellulose lithium salt (CMC-Li4) obtained using CMC-H4 was 0.70, and the viscosity of a 1% by mass aqueous solution measured with a B-type viscometer at 25°C was 3,860 mPa s.

[0092] The measurement and evaluation results in the examples and comparative examples are shown in Table 1 below.

[0093] [Table 1]

[0094] As shown in Table 1, the battery obtained by using the lithium carboxymethylcellulose salt having a carboxymethyl substitution degree of 0.5 to 2.0 per anhydrous glucose unit and containing 3,000 ppm or less of sodium ion per 1 g of the lithium carboxymethylcellulose salt had excellent battery capacity. In addition, it was shown that metal corrosion was particularly suppressed when nitric acid was used as the strong acid.

Claims

1. A lithium carboxymethyl cellulose salt having a degree of carboxymethyl substitution per anhydrous glucose unit of 0.5 to 2.0, wherein the amount of sodium ions contained in 1 g of the lithium carboxymethyl cellulose salt is 3,000 ppm or less.

2. The carboxymethylcellulose lithium salt according to claim 1, wherein the viscosity of a 1% by mass aqueous solution measured at 25 ° C. with a B-type viscometer (30 rpm) is 10 to 20,000 mPa · s.

3. Step (a): Adding a strong acid in the acidification reaction of carboxymethylcellulose or its sodium salt A method for producing a carboxymethyl cellulose lithium salt comprising the steps of: The method for producing the lithium carboxymethyl cellulose salt, wherein the lithium carboxymethyl cellulose salt has a degree of carboxymethyl substitution per anhydrous glucose unit of 0.5 to 2.0, and the amount of sodium ions contained in 1 g of the lithium carboxymethyl cellulose salt is 3,000 ppm or less.

4. The method for producing a carboxymethylcellulose lithium salt according to claim 3, wherein the strong acid is nitric acid.

5. Step (b): In the lithiation reaction after step (a), lithium hydroxide is added, followed by neutralization with acetic acid. The method for producing the carboxymethylcellulose lithium salt according to claim 3 or 4, comprising:

6. An electrode composition for a non-aqueous electrolyte secondary battery, comprising the carboxymethylcellulose lithium salt according to claim 1 or 2.

7. An electrode for a non-aqueous electrolyte secondary battery, comprising the electrode composition for a non-aqueous electrolyte secondary battery according to claim 6.

8. A non-aqueous electrolyte secondary battery using the electrode composition for a non-aqueous electrolyte secondary battery according to claim 6.

Citation Information

Patent Citations

  • Negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2015198038A

  • Carboxymethyl cellulose lithium with high viscosity, and methods for preparing the same and uses thereof

    JP2023008785A